Examining spatial identity of kampungs through young adults’ perception in Surabaya – Indonesia - Rully Damayanti; Florian Kossak (Journal of Architecture and Urbanism, 2016)
Spatial identity is a result of a connection between people, physical elements of places, and activities associated with them. The development of identity occurs through the psychological process place attachment. This article is based on a research project that observed the spatial identity of young adults living in kampungs (urban villages), in Surabaya city. The young adults are faced with the contrast of a two-sided modernity between the kampungs and the city, which affects their attachment. The study of place attachment has been undertaken through an observation of social life of the participants and spatial perception. Through this study of spatial identity not only physical characteristics were identified, but also social characteristics. This is due to physical conditions of space and social interactions in these spaces are intertwined. The study found that the identity with the strongest attachment is related to social behaviour of the young adults but which is not recognised by current planning strategies. This study of spatial identity is suggesting that policy changes are needed to improve spatial environment of the kampungs.